2002
DOI: 10.1084/jem.20011783
|View full text |Cite
|
Sign up to set email alerts
|

The Ligand-binding Domain of CD22 Is Needed for Inhibition of the B Cell Receptor Signal, as Demonstrated by a Novel Human CD22-specific Inhibitor Compound

Abstract: CD22 is a B cell–specific transmembrane protein of the Siglec family. It binds specifically to α2,6-linked sialic acid (Sia) residues, which are also present on glycoproteins on the B cell surface. CD22 acts as a negative regulator in B cell receptor–mediated signaling by recruitment of Src homology 2 domain–containing tyrosine phosphatase (SHP)-1 to its intracellular tail. To analyze how ligand-binding of CD22 influences its intracellular signaling domain, we designed synthetic sialosides as inhibitors for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
145
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(158 citation statements)
references
References 29 publications
11
145
1
1
Order By: Relevance
“…In each case studied, these motifs can be tyrosine phosphorylated, recruit the protein tyrosine phosphatases SHP-1 and SHP-2, and trigger inhibitory signaling when cross-linked to activating receptors with mAb [3][4][5][6]. This suggests that the natural function of CD33-related siglecs is to modulate leukocyte activation, possibly in an analogous fashion to the inhibitory receptor CD22/ siglec-2 on B cells [7][8][9]. Other studies have indicated that CD33-related siglecs may potentially regulate leukocyte proliferation and apoptosis through unknown mechanisms [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In each case studied, these motifs can be tyrosine phosphorylated, recruit the protein tyrosine phosphatases SHP-1 and SHP-2, and trigger inhibitory signaling when cross-linked to activating receptors with mAb [3][4][5][6]. This suggests that the natural function of CD33-related siglecs is to modulate leukocyte activation, possibly in an analogous fashion to the inhibitory receptor CD22/ siglec-2 on B cells [7][8][9]. Other studies have indicated that CD33-related siglecs may potentially regulate leukocyte proliferation and apoptosis through unknown mechanisms [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Siglecs recognize sialic acid, a nine-carbon sugar that often caps the non-reducing end of glycans (4). Engagement of specific sialylated ligands by siglecs is thought to influence cellular adhesion, recognition, and signaling in the immune and nervous systems (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The Sia␣2-6Gal sequence recognized by CD22 is differentially expressed in a cell typespecific manner (8)(9)(10) and is abundant on B and T lymphocytes (11,12). Several reports have suggested that the ligand-binding domain of CD22 can modulate its activity as a regulator of B cell signaling (5,(13)(14)(15). Although the precise ligand interactions that modulate CD22 function are not well understood, both cis (B cell) and trans (opposing cell) glycoprotein ligands appear to be important.…”
mentioning
confidence: 99%
“…Indeed, inhibition of CD22 binding to cis ligands by using small molecule ligand mimics (14) or abrogation of its binding by site directed mutagenesis results in decreased SH2 domain-containing phosphatase 1 (SHP-1) recruitment and increased calcium flux after B cell receptor (BCR) crosslinking in vitro (15). CD22 can bind to a variety of B cell glycoproteins in vitro, including CD45 and IgM, which are often cited as potentially important functional cis ligands of CD22 (28).…”
mentioning
confidence: 99%